A study of application of western strategic management model for small medium enterprise (SMEs) in the northern states of Malaysia and propose of a revised model - Cheng, Wei Hin; Abdullah, Haim Hilman; Abdul Kadir, Kadzrina (Universiti Utara Malaysia, 2011)
The study was aimed to examine whether small medium enterprise (SME) in the northern states of Malaysia do strategic planning and if they do, does the Wheelen and Hunger (2008) model applies to them.Furthermore, the study also suggests some improvement to the model.A total of 108 respondents which are SMEs from Perlis, Kedah and Penang participated in this research.Results for the study showed that SMEs do have strategic planning and more than half said that their strategic planning process resembles the strategic planning model of Wheelen & Hunger (2008).The strategic planning process of the SMEs in the northern states of Malaysia is not much different from that of the Wheelen & Hunger (2008) proposed model.